METHODS OF MEASURING THE LEVEL OF COMMUNICATION EFFICIENCY IN NEWS HEADLINES: (Drawn from the doctoral thesis) - Al-Rubaie, Akram Faraj (ALBAHITH ALALAMI, 2012)
Measuring the level of communicative competence in news headlines and the level of stylistic and semantic processing in its formulation requires creating a quantitative scale based on the bases on building the scales and their standards. As judging by scientific of journalism studies lies in the possibility of quantifying the journalistic knowledge, i.e. the ability of this knowledge to shift from qualitative language to its equivalent in the language of numbers. News headlines and editorial processing are one of the journalistic knowledges that should be studied, analyzed stylistically and semantically; their conclusions drawn and expressed in numbers. Press knowledge is divided into two types: First: Knowledges related to the means element means the newspaper, whether a newspaper or magazine. Second: Knowledges related to the sender, message, receiver, echo or impact elements. The news headline measure to be developed depends on the division of these types of journalistic knowledge according to the elements of the communication process. It measures the efficiency of each of its components as follows: • Stylistic and semantic measurement of the media message in the form of news headlines: It includes a set of mathematical equations that adopt the ratio and proportionality system developed by the researcher for the purpose of accomplishing the measurement of the effectiveness of the headlines published in newspapers and their level of communication efficiency. This measurement represents the press knowledge related to the element of the message. • Measure the level of communication skills of press editors with regard to stylistic and semantic processing in formulating the news headlines using the test model prepared by the researcher for the purpose of completing this measurement of twenty questions and each question estimate five grades. In this light, the degree of drafting skill of news editors is determined. And this measurement represents journalistic knowledge related to the sender’s element. Communication skill is matched by craft and intelligence. It means upgrading the meanings positively, excitement and conciseness in order to reach balance with the form of the method used; and to provide meaning in harmony and rhythm. Communication skills mean writing and speaking skills on the one hand; and reading and listening skills on the other hand, i.e. the ability of the writer or speaker as the sender or source to choose linguistic and non-linguistic symbols; as well as the ability of the recipient to convert the symbols received to meanings he/ she can understand and grasp. This process is called coding skills. • Determining the preference of the formulas in the news headlines resulting from the treatment taken by the editor that achieve the means of attracting attention and interest of the reader using the semantic differentiation form prepared by the researcher to identify the preference of the formulations used in the headlines of the readers that attract their attention and interest in the news. This measurement represents journalistic knowledge related to the elements of the future and echo. • Identifying the newspapers whose titles are subject to the study according to the research plan and objectives; measuring the efficiency of drafting the titles; and presenting and diagnosing the type of journalism school to which it belongs. This measurement represents journalistic knowledge related to the instrument element.